Analysis of hydrophysical properties of soils using pore-network models - K. D. Tolstygin; D. S. Fomin; A. V. Yudina; K. M. Gerke (Бюллетень Почвенного института им. В.В. Докучаева, 2025)
Modern soil physical models traditionally consider the pore space as static; however, new visualization techniques, such as X-ray tomography, have revealed structural dynamics that can intensively change under the influence of moisture and temperature. The aim of this study is to investigate the structure of the pore space using pore network models (PNMs) and to compare them with the method of the water retention curve (WRC). The study was based on the laboratory experiment involving the wetting and drying of samples of Haplic Chernozem from the Kursk region, with measurements of WRC and registration of the soil structure state using X-ray computed tomography (XCT). From the 3D soil images, PNMs were extracted, for which hydrophysical properties were calculated, including modeling of the WRC and the water conductivity. The comparison of pore sizes and volumes shows a significant excess of the pore volume calculated based on WRC measurements, compared to direct geometry measurements by XCT. The difference in the representation of the pore space is expressed through significant differences in modeling of water conductivity based on PNMs in the regions of low and high capillar pressure (large and small pore sizes, respectively) compared to the approach based on WRC modeling using the van Genuchten and van Genuchten-Mualem equations. However, the curves of relative unsaturated hydraulic conductivity measured using PNMs and based on WRC show a high degree of similarity. Based on the results of the study, it was demonstrated that modeling soil hydrophysical properties using PNMs is a highly promising approach and has the potential to be a more reliable tool for modeling water dynamics than the approach based on describing WRC using the van Genuchten equation. Nevertheless, the fundamental differences between the methods leave several questions open that require answers before the widespread use of PNMs for calculation of soil hydrophysical properties.